Australian gay men describe the details of their HIV infection through a cross-sectional web-based survey - Down, I.; Prestage, G.; Ellard, J.; Triffitt, K.; Brown, Graham; Callander, D. (Journal of Medical Internet Research, 2016)
Background: With emerging opportunities for preventing human immunodeficiency virus (HIV) transmission, it remains important to identify those at greatest risk of infection and to describe and understand the contexts in which transmissions occur. Some gay and bisexual men with recently diagnosed HIV infection are initially unable to identify high-risk behaviors that would explain their HIV infection. We explored whether Web-based data collection could assist them in identifying the circumstances of their infection. Objective: To assess the capacity of a Web-based survey to collect reliable self-report data on the event to which gay and bisexual men ascribe their HIV infection. Methods: The HIV Seroconversion Study included a Web-based survey of gay and bisexual men with recently diagnosed HIV infection in Australia. Participants were asked if they could identify and describe the event they believe led to their infection. Men were also asked about their sexual and other risk practices during the 6 months before their diagnosis. Results: Most (403/506, 79.6%) gay and bisexual men with newly diagnosed HIV infection were able to identify and describe the circumstances that likely led to their infection. Among those who were initially unable to identify possible exposure events, many could nonetheless provide sensible information that ostensibly explained their seroconversion. Free-text responses allowed men to provide more detailed and contextual information, whereas questions about the totality of their sexual behavior before diagnosis provided opportunities for men to describe their sexual risk behavior in general. Overall, 84.0% indicated having engaged in condomless anal intercourse before their HIV diagnosis, including 71.8% in the receptive position. Conclusions: This study demonstrates the effectiveness of using Internet-based technologies to capture sensitive information about the circumstances in which HIV infection occurs among gay and bisexual men. By providing a range of opportunities for relaying experience, this research reveals some of the complexity in how individuals come to understand and explain their HIV infection. These findings may assist in obtaining detailed sexual history in the clinical setting.